The Influence of Motivation on the Decision to Choose a Collage of Administrative Sciences in South Kalimantan Using Electronic Word of Mouth (EWOM) as an Intervening Variable - Cici Asmawatiy; Laila Refiana Said (PT FORMOSA CENDEKIA GLOBAL, 2023)
Electronic Word of Mouth (EWOM) is formed from the opinions of a consumer, potential customer, and former customer. This study aims to analyze the effect of Motivation on the decision to choose a high school of administrative science in South Kalimantan, with electronic word of Mouth as an intervening variable. This study used a quantitative research approach, with the object of research being students of High Schools majoring in Administrative Sciences in South Kalimantan, namely STIA Bina Banua Banjarmasin, Amuntai, and Tabalong. The analytical method uses Structural Equation Modeling and offers Path analysis capabilities. The path analysis used in this research is Partial Least Squares (PLS), using Smartpls. The results of the study show that Motivation has a significant effect on Electronic Word of Mouth (e-WoM). Electronic Word of Mouth (e-WoM) influences Voting Decisions.